ANALISIS KINERJA KEUANGAN PADA PT. MAJU WIRA PERSADA PALEMBANG - Khofifah Rahma; Iskandar Sam; Misni Erwati (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2023)
Efforts to improve financial performance can be achieved if the company can optimize the success of its value creation. Increasing company value is expected to influence the company's ability to guarantee the welfare of the parties involved. This study aimed to determine the company's financial performance as measured using financial ratio analysis at PT. Maju Wira Persada Palembang for the period 2018 – 2022. The data analysis is a quantitative descriptive method using financial ratio measurements in the form of liquidity, solvency, activity and profitability ratios. Research shows that the liquidity ratio of PT. Maju Wira Persada Palembang is in the good category. PT. solvency ratio Maju Wira Persada Palembang is in the good category. PT. activity ratio Maju Wira Persada Palembang is in the pretty good category. PT. Maju Wira Persada Palembang is in the unfavorable category.